Health‐Related Quality of Life in Cancer Survivors with Chemotherapy‐Induced Peripheral Neuropathy: A Randomized Clinical Trial. (26th August 2021) - Bao, Ting; Baser, Raymond; Chen, Connie; Weitzman, Matthew; Zhang, Yi Lily; Seluzicki, Christina; Li, Qing Susan; Piulson, Lauren; Zhi, W. Iris
Abstract: Background: Chemotherapy‐induced peripheral neuropathy (CIPN) is a common, debilitating adverse effect of neurotoxic chemotherapy that significantly worsens the quality of life of cancer survivors. Materials and Methods: Survivors of solid tumors with persistent moderate‐to‐severe CIPN defined as numbness, tingling, or pain rated ≥4 on an 11‐point numeric rating scale (NRS) were randomized in a 1:1:1 ratio to 8 weeks of real acupuncture (RA) versus sham acupuncture (SA) versus usual care (UC). We previously reported the primary endpoint (NRS); here we report the following health‐related quality of life endpoints: Functional Assessment of Cancer Therapy/Gynecologic Oncology Group‐Neurotoxicity (FACT/GOG‐Ntx), Hospital Anxiety and Depression Scale (HADS), Insomnia Severity Index (ISI), and Brief Fatigue Inventory (BFI). For each endpoint, the mean changes from baseline and 95% confidence intervals were estimated within each arm and compared between arms using linear mixed models. Results: We enrolled 75 survivors of solid tumors with moderate‐to‐severe CIPN into the study. Compared with baseline, at week 8, FACT/GOG‐Ntx, HADS anxiety, and ISI scores significantly improved in RA and SA, but not in UC. Compared with UC, at week 8, FACT/GOG‐Ntx scores significantly increased in RA and SA arms indicating improved CIPN‐related symptoms and quality of life ( p  = .001 and p  = .01). There was no statistically significant difference between RA and SA. There was no difference in HADS depression or BFI among RA, SA, and UC at weeks 8 and 12. Conclusion: Acupuncture may improve CIPN‐related symptoms and quality of life in cancer survivors with persistent CIPN. Further large sample size studies are needed to delineate placebo effects. Implications for Practice: The authors conducted a randomized sham acupuncture‐ and usual care‐controlled clinical trial to evaluate the impact of acupuncture on health‐related quality of life outcomes in patients with solid tumors with chemotherapy‐induced peripheral neuropathy (CIPN). Statistically significant improvements in quality of life, anxiety, insomnia, and fatigue were achieved with 8 weeks of real acupuncture when compared with baseline, without statistically significant differences between real and sham acupuncture. These findings suggest that acupuncture may be effective for improving CIPN‐related symptoms and quality of life and reducing anxiety and insomnia in cancer survivors with persistent CIPN, with further study needed to delineate placebo effects. Abstract : Acupuncture is a promising and safe nonpharmacological approach to potentially address the unmet need for an effective treatment of chemotherapy‐induced peripheral neuropathy. This article reports the results of a randomized sham acupuncture‐ and usual care‐controlled clinical trial to evaluate the effect of acupuncture on health‐related quality of life outcomes in patients with solid tumors dealing with chemotherapy‐induced peripheral neuropathy.